PENGARUH VARIABEL MAKROEKONOMI TERHADAP PENINGKATAN PENERIMAAN PENDAPATAN ASLI DAERAH KOTA PEKANBARU - Muhammad Surya Anggara; Syafril Basri; Deny Setiawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The research aim to know the influence of macroeconomic variables to the regional revenue in Pekanbaru City. The data used in this research is the data time series from 1995 until 2015. This research was in Pekanbaru City was chosen based on the consideration that Pekanbaru City is one metropolitan city that has high economic growth. The data collected from data GDP (Gross Domestic Product), constant price, population, the inflation rate and income revenue. The data obtained from Badan Pusat Statistik (BPS), Pekanbaru city in figures. Method of analysis used was multiple linear regression analysis.The research result obtained that the variable GDP, population, and the inflation rate simultaneously significant influence to the regional revenue in Pekanbaru City, as much as 134,513 with the significant level 0,000.Of the individual test result with significant levels of partial (α) obtained 5% of the variable GDP and population have a positive influence and significant to the regional revenue with each value are 6.431 and 6.080 , while the inflation rate has a negative influence and not significant, as much as -0,302. The magnitude of the influence that caused (R2) by both these variables simultaneously against the variable dependent was 96%, 4% while the rest is affected by other variables not in meticulous in this research.Keyword: GDP, population, the inflation rate, Receiving the Regional Revenue(PAD)